(untitled) (Journal of Basic and Applied Research in Biomedicine, 2022)
Four novel parsley genotypes (Moskurl 2 Petra, Moskurl 2 KRA USA, Gewone Dai 3 Rial 10, and Bravour) were imported from Netherlands to be planted and evaluated along with the Egyptian local variety “Egyptian” in the sandy soil under the Middle Egypt growing conditions. Three of the four introduced genotypes are curly-leafed varieties and one is non-curly leafed “Gewone Dai 3 Rial 10” as well as the Egyptian is a non-curly leafed variety. The aims of this experiment were to evaluate and study the growth characteristics (e.g. plant height, plant fresh and dry weights and fresh yield of leaves/m2) and some chemical properties of these genotypes (e.g. TSS and essential oil contents, essential oil composition and leaves content of chlorophyll a, b, and carotenoids) after adaptation and growing during the two successive winter seasons of 2013/2014 and 2014/2015. All introduced genotypes grew very well under these conditions and showed a very acceptable vegetative growth, profitable yield and high levels of volatile oils rich in anticancer and flavor responsible compounds and their horticultural and chemical proprieties were compared with those of the Egyptian local variety. The obtained data are very promising for Egyptian parsley growers to produce these new imported varieties in order to meet the increasing demand of parsley fresh and dry processed products with different shapes and different tastes of the Egyptian and foreign markets.